High-Fidelity MC-DEM Modeling and Uncertainty Analysis of HTR-PM First Criticality - Li, Ruihan; Liu, Zhaoyuan; Feng, Zhiyuan; Liang, Jingang; Zhang, Liguo (Frontiers in Energy Research, 2022)
A high-fidelity model for the first criticality of pebble-bed reactor HTR-PM is built using Monte Carlo (MC) code RMC and Discrete Element Method (DEM) code LAMMPS. Randomly packed TRISO particles and fuel pebbles are modeled explicitly. Cone structure on the top of pebble bed is also taken into account. Criticality calculation result agrees well with the experiment. Uncertainty analysis is carried out considering three inherent aspects: the randomness of MC code; the randomness of TRISO and pebble position; and the randomness of mixed pebbles. Results show that these factors have a significant impact on the uncertainty of effective multiplication factor (keff). And the most influential factor is expected to be the randomness of mixed pebbles. The influence of several configuration factors is studied as well. It is observed that the effects of cross-section library, the heterogeneity of TRISO, and the angle of pebble bed cone are nonnegligible contributors. However, results between randomly and regularly placed TRISO are not noticeably different.